Analisis Pragmalingusitik Terhadap Peribahasa Nasihat Minangkabau - Mutia Irhamni (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to analyze Minang advice proverbs pragmatically and syntactically. Minang advice proverbs pragmatically have a distinctive meaning, and syntactically can be analyzed by complexity type, voice and mood. The research method uses qualitative-quantitative. With the research theory of Searle (1969) and Bach Harnish (1979), the theory used is to analyze the speech act function of Minang Kabau advice proverbs based on locution, illocutionary perlocution, felicity function and directive derivative function and communicative function of meaning of Minang Kabau advice proverbs to syntactic function. The data is sourced from a book by Idrus Hakim entitled